2023
DOI: 10.1101/2023.01.19.23284696
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nuclear genetic control of mtDNA copy number and heteroplasmy in humans

Abstract: Human mitochondria contain a high copy number, maternally transmitted genome (mtDNA) that encodes 13 proteins required for oxidative phosphorylation. Heteroplasmy arises when multiple mtDNA variants co-exist in an individual and can exhibit complex dynamics in disease and in aging. As all proteins involved in mtDNA replication and maintenance are nuclear-encoded, heteroplasmy levels can, in principle, be under nuclear genetic control, however this has never been shown in humans. Here, we develop algorithms to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 106 publications
0
18
0
Order By: Relevance
“…Using the GWAS summary statistics for both raw and adjusted blood mtDNA-CN from Gupta et al, 2023 9 , we constructed the polygenic risk scores (PRSs) per individual in AMP PD (Supplementary Table 1C). Subsequently, we assessed the relationships between the actual mtDNA-CN estimates and these PRSs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the GWAS summary statistics for both raw and adjusted blood mtDNA-CN from Gupta et al, 2023 9 , we constructed the polygenic risk scores (PRSs) per individual in AMP PD (Supplementary Table 1C). Subsequently, we assessed the relationships between the actual mtDNA-CN estimates and these PRSs.…”
Section: Resultsmentioning
confidence: 99%
“…9). This modest correlation can be attributed to the fact that mtDNA-CN is influenced by both genetic and environmental factors, with a SNP-based heritability of approximately 4% 9 . Additionally, the PRSs exhibit no correlation with mtDNA-CN estimates from brain samples (Supplementary Table 1D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Restabilizing the mitochondrial tRNA structures may also be useful, Perli et al utilized exogenous peptides to stabilize the mitochondrial tRNA structures, which rescued the defects caused by m.3243A > G. While the mitochondrial mutant influences multiple downstream pathways 8 , Chung et al found that the inhibition of PI3K, Akt, or mTORC1 could reduce the mtDNA mutant load and partially rescue cellular bioenergetic function 55 . In a GWAS of human mitochondrial DNA, the authors found 92 nuclear loci could control the copy number and heteroplasmy of mitochondrial DNA in humans 56 , indicating that nuclear loci may also play a regulatory role in the effect of m.3243A > G.…”
Section: Discussionmentioning
confidence: 99%
“…found that the inhibition of PI3K, Akt, or mTORC1 could reduce the mtDNA mutant load and partially rescue cellular bioenergetic function 55 . In a GWAS of human mitochondrial DNA, the authors found 92 nuclear loci could control the copy number and heteroplasmy of mitochondrial DNA in humans 56 , indicating that nuclear loci may also play a regulatory role in the effect of m.3243A > G.…”
Section: Discussionmentioning
confidence: 99%